2018
DOI: 10.7150/ijms.23402
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-135b Contributes to Triple Negative Breast Cancer Molecular Heterogeneity: Different Expression Profile in Basal-like Versus non-Basal-like Phenotypes

Abstract: The clinical and genetic heterogeneity of Triple Negative Breast Cancer (TNBC) and the lack of unambiguous molecular targets contribute to the inadequacy of current therapeutic options for these variants. MicroRNAs (miRNA) are a class of small highly conserved regulatory endogenous non-coding RNA, which can alter the expression of genes encoding proteins and may play a role in the dysregulation of cellular pathways. Our goal was to improve the knowledge of the molecular pathogenesis of TNBC subgroups analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…By contrast, we observed CpG promoter hypomethylation and upregulation of miR-135b in ER-versus ER + tumors. Consistent with these results, several studies have reported miR-135b was upregulated in ER-or triple negative breast cancers and its overexpression promotes breast cancer progression and metastasis through regulation of ERα, AR, and other genes such as LATS2, TGFβ, WNT, and HIF1AN (37)(38)(39)(40)(41). Taken together, con rmed in TCGA data, these consistent negative correlations between CpG methylation and miRNA expression support the notion that, at least in some cases, altered miRNA expression may occur through mechanisms involving loss or gain of promoter DNA methylation during early stages of carcinogenesis and contribute to the development of speci c subtypes of the disease.…”
Section: Discussionsupporting
confidence: 73%
“…By contrast, we observed CpG promoter hypomethylation and upregulation of miR-135b in ER-versus ER + tumors. Consistent with these results, several studies have reported miR-135b was upregulated in ER-or triple negative breast cancers and its overexpression promotes breast cancer progression and metastasis through regulation of ERα, AR, and other genes such as LATS2, TGFβ, WNT, and HIF1AN (37)(38)(39)(40)(41). Taken together, con rmed in TCGA data, these consistent negative correlations between CpG methylation and miRNA expression support the notion that, at least in some cases, altered miRNA expression may occur through mechanisms involving loss or gain of promoter DNA methylation during early stages of carcinogenesis and contribute to the development of speci c subtypes of the disease.…”
Section: Discussionsupporting
confidence: 73%
“…Previously, miR-135b-5p has been well documented as a tumor suppressor [33][34][35] or oncogene [36][37][38] in breast cancer, but less is known about the expression and function of miR-135b-3p. In case that both 5p and 3p strands are functional and not degraded, despite targeting different mRNAs, they might cooperate temporally and result in a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-135b overexpression was highly related to TNBC with BLP and played a role in the TGF-beta, WNT, and HER2 pathways, confirming its involvement in TNBC with BLP pathogenesis. The miR-135b overexpression had a negative prognostic role that might be linked to a positive correlation with elevated proliferative index: modification of miR-135b expression could represent a therapeutic target in basal-like TNBCs [74]. Furthermore, previous studies showed miR-135b overexpression in TNBC and its downregulation in luminal tumors [18,[75][76][77].…”
Section: Microrna Dysregulation On Tnbc With Basal-like Phenotype: Anmentioning
confidence: 87%
“…Cell proliferation, AR status, and age [18,[74][75][76]139] miR-421 PIEZO2, PDCD4 Cell proliferation [156] miR-454-3p PIEZO2, AKT Cell proliferation, migration, invasion, and apoptosis [156] miR-301a-3p, PTEN, ER, PIEZO2…”
Section: Dnmt3bmentioning
confidence: 99%